Pendekatan Pembelajaran Saentifik Dalam Pembelajaran IPS - Ita Fatihatun Najihah; Melda Astiyana; Oman Farhurahman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The purpose of this study is to determine the influence of scientific methods on the learning outcomes of social studies students. The type of research used is data collection research using journals, books, and others. Based on the results of research and discussion on the effectiveness of scientific methods. The scientific method is considered a golden bridge that encourages the development of attitudes, skills, and knowledge in students. The application of the scientific method provides challenges to teachers by developing student activities, namely observing, asking, gathering information, reasoning, and communicating. Social studies with scientific methods. Learning is not just memorizing concepts, years, or facts, but trying to connect these concepts so that they produce a complete understanding so that the concepts learned are easy to understand.